Classroom Environment and Metacognitive Strategies to Support Beginning Reading Skills: A Systematic Literature Review - Durroh, Lum’Atud; Raharjo, Tri Joko; Harianingsih, Harianingsih; Sumbali, Bambang; Widiarti, Nuni (Papanda Publisher, 2025)
This study presents a systematic literature review examining the role of the classroom environment in developing beginning reading skills among primary school students. The review covers 20 national and international journal articles published between 2020 and 2025. The articles were selected based on predefined inclusion criteria (studies that explicitly investigated the influence of classroom environment on reading skills of primary school children, were empirical in nature, and were published in peer-reviewed journals) and exclusion criteria (articles that were non-empirical, were review or opinion papers, or addressed unrelated skills or age groups). Data were gathered through structured searches in Scopus, Web of Science, and Google Scholar databases using keywords such as “reading,” “classroom environment,” and “early literacy.” The search strategy involved combinations of these keywords to maximize retrieval of relevant articles. The findings reveal that both physical and non-physical aspects of the classroom environment, such as seating layout, lighting, social interaction, emotional support, and teacher-student relationships, are critical in enhancing students’ reading readiness, word recognition, fluency, and comprehension. Most articles report that well-organized classrooms with adequate reading resources, supportive emotional climates, and interactive learning settings foster increased student engagement and motivation. Additionally, approaches such as peer-assisted learning, multisensory methods, and differentiated instruction, when integrated into a conducive classroom environment, further support literacy development. Several studies also demonstrate measurable improvements in student performance after environmental modifications, including increased reading scores and more substantial interest in learning. This review offers insight into how classroom conditions significantly impact literacy outcomes and provides practical recommendations for educators to design learning spaces that encourage reading skill acquisition in the early grades. The findings may guide future research and inform teaching strategies to support foundational literacy in primary education.